(3GddhGeY GdZjHjI (B( (3aj GdQhM (B)s - (3TgGH GdOjf CHh MaU YeQ Hf eMeO Hf YHO Gddg GdSgQhQOj GdTGaYj, GdSgQhQOj,J (B632 (3g` s
(3ChdgG (B:s
(3bGd Gddg JYGdi hjSCdhfc Yf GdQhM bd GdQhM ef GeQ QHi heG GhJjJe ef GdYde GdG bdjdG s
(3BNQgG (B:s
(3hUGHQJ GdfaS eY GdLSO Hjf jOi GdMb YGdejf HGdMb YGHOjf ddMb Pdc JbOjQ GdYRjR GdYdje hGddg GYde s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(3/594) s
Keywords: (3GdadSaI hGdefWbs